MnO2 nanowires anchored on amine functionalized graphite nanosheets: highly active and reusable catalyst for organic oxidation reactions. Issue 112 (28th October 2015) - Chakravarty, A.; Sengupta, D.; Basu, B.; Mukherjee, A.; De, G.
Abstract : MnO2 nanowires were synthesized on amine functionalized graphite nanosheet and excellent catalytic efficiency of as-prepared composite towards organic oxidation reactions was demonstrated. Abstract : A facile method of synthesizing MnO2 nanowires on amine functionalized graphite nanosheet (AFGNS) has been accomplished. A probable mechanism has been proposed where the –NH2 groups on the AFGNS surface create a weakly basic environment assisting the reduction of KMnO4 to MnO2 nanoparticles followed by their anchoring and oriented growth to form MnO2 nanowires. The as prepared MnO2 @AFGNS composite has been efficiently used as a selective heterogeneous catalyst for oxidation of primary and secondary benzyl alcohols to corresponding carbonyl compounds under aerobic condition in high yields in the absence of any other oxidizing or activating agent. While MnO2 is considered as the most efficient and selective catalyst for the oxidation of benzyl and allyl alcohols, its large excess use (200 mol% with respect to the substrate) has been circumvented in this work by using heterogeneous AFGNS supported MnO2 (only 7 mol% with respect to the substrate). The synergistic effect between the 1-D MnO2 nanowires and AFGNS facilitates very fast e − transfer enabling such huge enhancement of the catalytic activity of the MnO2 @AFGNS composite. The composite also shows sufficient reuse capability and stability after 3 cycles of catalysis thus making it a potentially cheap and active catalyst in the field of organic catalysis.